ANALYSIS OF FACTORS AFFECTING THE PERFORMANCE OF AGRICULTURAL EXTENSION WORKERS AT THE AGRICULTURAL EXTENSION CENTER (BPP) OF DEWANTARA DISTRICT, NORTH ACEH REGENCY - Nopri Yanto; Eva Wardah; Setia Budi; Cut Rozanasari; Rinaldi; Wahyu Isnanda Nasution (LPPM Universitas Malikussaleh - Indonesia, 2026)
Agriculture is a key sector that contributes significantly to the economy of North Aceh and the Province of Aceh as a whole. As one of the agricultural centers in the region, North Aceh has great potential to increase agricultural production and improve farmers' welfare. In this context, agricultural extension workers play a strategic role as a bridge between the latest agricultural technologies and field-level farming practices. This study aims to analyze the influence of age, formal education, work experience, distance to the working area, and the number of assisted villages on the performance of agricultural extension workers. The research location was determined purposively. The data were analyzed using multiple linear regression analysis, which was applied to examine the influence of several independent variables on the dependent variable. The study was conducted from June 2025 to November 2025. The results show that the performance of agricultural extension workers at the Agricultural Extension Center (BPP) of Dewantara, North Aceh District, is categorized as high. Internal and external factors simultaneously have a significant effect on the performance of agricultural extension workers. However, only formal education and age have a significant effect, while work experience, distance to the working area, and the number of assisted villages do not have a significant partial effect on the performance of agricultural extension workers at the Agricultural Extension Center (BPP) Dewantara, North Aceh District. Keywords: Performance of Agricultural Extension Workers and Extension Workers.